Ilmu dalam Tinjauan Filsafat: Ontologi, Epistemologi, dan Aksiologi - Munip, Al (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
Science has specific components, such as objects, statements, propositions, and characteristics. These four aspects are the focus of three philosophical foundations: ontology, epistemology, and axiology. This article is written to discuss science from a philosophical perspective, namely ontology, epistemology, and axiology. In this article, the author uses the literature study method by reviewing various books and other scholarly works relevant to the topic discussed. From the analysis, it can be concluded that ontology focuses on the nature of "being." In ontological studies, science aims to prove and examine the existence of a particular knowledge. Epistemology addresses the foundation of knowledge, including its sources, characteristics, truth, and methods of acquisition. From the epistemological perspective, the discussion of science centers on the sources and methods used by scientists to develop knowledge. Axiology deals with the relationship between science and values, evaluating the appropriateness of developing certain knowledge based on existing values.